Representing Vilnius Dispute in Polish History Textbooks from 1989 to 2022 (Relevant Tomorrow / Aktualu rytoj, 2022)
The school is one of the first places where one learns about the common history of neighboring countries. In the history of bilateral relations between Poland and Lithuania, the conflict over the Vilnius region can be singled out, as it had a significant impact on the newly emerging relations between the two countries in the 1990s. The aim of this article is to analyze the representation of Vilnius dispute in Polish history textbooks in 1989-2022, identifying the features of the content of the topic, the changes and the factors that may have influenced it. For this purpose, I analyze thirty-seven Polish history textbooks related to the issue. The study had shown that some textbooks from the 1990s reflected the prevailing attitude in interwar Polish historiography, which emphasized cooperation between Lithuania and the Bolsheviks and the significance of Poland’s successful war with Soviet Russia for Lithuania’s independence. Nevertheless, the majority of the authors of the textbooks in question chose not to be partisan and presented the statements related to Vilnius dispute in a neutral way. The 21st-century textbooks were more likely to explain Lithuania’s aspiration to regain Vilnius on the basis of the desire to recover its historical capital.
Keywords: Vilnius dispute; Polish history textbooks in the turn of the 21st century; Polish history curricula; history didactics